Peptides targeting chemokine receptor CXCR4: structural behavior and biological binding studies†. (28th January 2014) - Costantini, Susan; Raucci, Raffaele; Colonna, Giovanni; Mercurio, Flavia Anna; Trotta, Anna Maria; Paola, Ringhieri; Leone, Marilisa; Rossi, Filomena; Pellegrino, Carmela; Castello, Giuseppe; Scala, Stefania
<x xml:space="preserve">Abstract</x> CXCR4 is a G‐protein‐coupled receptor involved in a number of physiological processes in the hematopoietic and immune systems. CXCL12/CXCR4 axis plays a central role in diseases, such as HIV, cancer, WHIM syndrome, rheumatoid arthritis, pulmonary fibrosis, and lupus and, hence, indicated as putative therapeutic target. Although multiple CXCR4 antagonists have been developed, there is only one marketed drug, plerixafor, indicated for stem cell mobilization in poor mobilizer patients. In this work, we have designed and synthesized two peptides, six and seven residues long, using as template the N‐terminal region of CXCL12; analyzed their conformations by CD, NMR, and molecular dynamics simulations; simulated their complexes with CXCR4 by docking methods; and validated these data by in vitro studies. The results showed that the two peptides are rather flexible in aqueous solution lacking ordered secondary structure elements and present a promising affinity for CXCR4. This affinity is not revealed for CXCR7, indicating a specificity for CXCR4. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.